2007
DOI: 10.2353/ajpath.2007.060969
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Carcinoma and Embryonic Cytotrophoblast Cell-Specific Mig-7 Induces Invasion and Vessel-Like Structure Formation

Abstract: Molecular requirements for carcinoma cell interactions with the microenvironment are critical for disease progression but are poorly understood. Integrin ␣v␤5, which senses the extracellular matrix, is important for carcinoma cell dissemination in vivo. ␣v␤5 signaling induces Mig-7, a novel human gene product that is apparently carcinoma-specific. We hypothesized that Mig-7 expression facilitates tumor cell dissemination by increasing invasion and vasculogenic mimicry. Results show that embryonic cytotrophobla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
64
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(69 citation statements)
references
References 52 publications
5
64
0
Order By: Relevance
“…Taken together, these observations suggest that high expressions of MIG-7 in tumor tissues concurrent with high expression of VE-cadherin may have a synergistic effect that promotes VM formation. Similar results were reported by Petty et al [17] when these investigators analyzed MIG-7 expression in breast cancer. They have demonstrated the specificity of MIG-7 expression to breast cancer tissue as MIG-7 was not detected in normal breast tissues nor it was found in blood from normal subjects.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Taken together, these observations suggest that high expressions of MIG-7 in tumor tissues concurrent with high expression of VE-cadherin may have a synergistic effect that promotes VM formation. Similar results were reported by Petty et al [17] when these investigators analyzed MIG-7 expression in breast cancer. They have demonstrated the specificity of MIG-7 expression to breast cancer tissue as MIG-7 was not detected in normal breast tissues nor it was found in blood from normal subjects.…”
Section: Discussionsupporting
confidence: 89%
“…To date, MIG-7 protein was found to be localized on normal embryonic cytotrophoblast cells and on cancer cells as well as within the lumen of vessel-like structures. Immunohistochemistry demonstrated that MIG-7 protein co-localizes with endothelial marker factor VIII, VE-cadherin and laminin 5 γ2 domain fragment III [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue of The American Journal of Pathology, Petty et al report that expression of a relatively understudied protein called migration-inducing protein 7 (MIG7 or Mig-7) facilitates tumor cell dissemination by increasing invasion and promoting the process of vasculogenic mimicry. 1 Vessels that form during tumorigenesis are usually lined by an endothelium, but abnormal vessel development in which cancer cells directly line vessels or blood channels within tumors have been described and termed vasculogenic mimicry. [2][3][4][5] One of the earliest descriptions of these tumor-lined vasculogenic channels was by Willis, who stated in 1948 that "in rapidly growing tumors, [vessels] consist of little more than irregular channels lined by endothelium only or by naked tumor cells.…”
mentioning
confidence: 99%
“…1 However, the complete pathophysiological significance of these structures in the tumorigenic process remains to be fully elucidated in animal models. 14 It is predicted that these structures may serve as an adjunct to the existing vasculature system, thereby aiding tumor growth as well as contributing to the metastatic process; however, this possibility remains controversial.…”
mentioning
confidence: 99%